2015
DOI: 10.1016/j.cmi.2014.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Special considerations of antibiotic prescription in the geriatric population

Abstract: Infectious diseases pose a major challenge in the elderly for two reasons: on the one hand the susceptibility to infection increases with age and when infections occur they often present atypically-on the other hand diagnostic uncertainty is much more pronounced in the geriatric population. Reconciling the opposing aspects of optimizing patient outcomes while avoiding antibiotic overuse requires significant expertise that can be provided by an infectious diseases consultant. In addition, geriatric facilities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 70 publications
1
62
0
14
Order By: Relevance
“…Explanations given for this hypothesis are altered physiological responses to the infecting pathogen in this patient group, and age-related changes in temperature regulation. 6 The results of studies reporting on sepsis presentation in the elderly and in comparison with younger patients are presented below (Table 1).…”
Section: Presentation Of Bsimentioning
confidence: 99%
See 4 more Smart Citations
“…Explanations given for this hypothesis are altered physiological responses to the infecting pathogen in this patient group, and age-related changes in temperature regulation. 6 The results of studies reporting on sepsis presentation in the elderly and in comparison with younger patients are presented below (Table 1).…”
Section: Presentation Of Bsimentioning
confidence: 99%
“…57 Contributing factors to high rates of colonization and infection of elderly with MDROs include substantial antimicrobial exposure, frequent hospitalizations, indwelling devices, dementia and low functional status, and as a result -high rates of cross transmission in these settings. 6,58 Dekinger et al demonstrated that among patients aged 65 and older admitted to hospital, rates of MDROs are approximately 2-fold higher for MRSA and vancomycin resistant enterococci (VRE) and 3-fold higher for multidrug resistant (MDR) Gram negative compared to younger patients. In this study, during 2009, 57% of Staph aureus isolates were methicillin resistant, 25% of enterococcal isolates were vancomycin resistant and 14% of gram-negative isolates were multidrug resistant.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
See 3 more Smart Citations